European multicenter evaluation of Xpert® Xpress SARS‐CoV‐2/Flu/RSV test. Issue 10 (6th June 2021) - Wolters, Femke; Grünberg, Maria; Huber, Michael; Kessler, Harald H.; Prüller, Florian; Saleh, Lanja; Fébreau, Christine; Rahamat‐Langendoen, Janette; Thibault, Vincent; Melchers, Willem J. G.
Abstract: Rapid diagnostics for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are paramount for reducing the spread of the current pandemic. During additional seasonal epidemics with influenza A/B and respiratory syncytial virus (RSV), the clinical signs and symptoms cannot be distinguished easily from SARS‐CoV‐2. Therefore, a new assay combining four targets in the form of the new Xpert Xpress SARS‐CoV‐2/Flu/RSV assay was evaluated. The assay was compared to the Xpert Xpress SARS‐CoV‐2, Xpert Xpress Flu/RSV, Seegene Flu/RSV, influenza A/B r‐gene® and RSV/hMPV r‐gene®. A total of 295 nasopharyngeal and throat swabs were tested at four institutes throughout Europe including 72 samples positive for SARS‐CoV‐2, 65 for influenza A, 47 for influenza B, and 77 for RSV. The sensitivity of the new assay was above 95% for all targets, with the highest for SARS‐CoV‐2 (97.2%). The overall correlation of SARS‐CoV‐2 Ct values between Xpert Xpress SARS‐CoV‐2 assay and Xpert Xpress SARS‐CoV‐2/Flu/RSV assay was high. The agreement between Ct values above 30 showed the multiplex giving higher Ct values for SARS‐CoV‐2 on average than the singleplex assay. In conclusion, the new assay is a rapid and reliable alternative with less hands‐on time for the detection of not one, but four upper respiratory tract pathogens that may circulate at the same time.